MICRODETERMINACION RAPIDA DEL AZUFRE EN SULFONAMIDAS - RAMIREZ, R; ERDOS, JOSE (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1948)
New complex compounds of Cu and ethylenediamine with sulfanilamide, sulfamethylthiazole, sulfathiazole and sulfadiazine were obtained, and some of their physical and chemical properties are givenTheir structural formulae are probably that of the chelates
AN ESC NAC CIENC BIOL
Keywords: MICRODETERMINACION RAPIDA, AZUFRE, SULFONAMIDAS; CIENCIAS DE LA VIDA; BIOFISICA; BIOMECANICA